An Analysis of Fricative Consonants of English Reading Used by the Fourth Semester of Manajemen Program Universitas PGRI Madiun - Theresia Budi Sucihati (STKIP PGRI Tulungagung, 2022)
This study examined incorrect spelling in fricative consonants by twenty participants in Manajemen Program Universitas PGRI Madiun's fourth semester class A. The students had difficulty pronouncing a letter in a word, particularly consonants. They are chosen as research subjects to discover the difficulties they have in pronouncing fricatives consonants in their speech, as well as how far they have progressed in producing the sounds. This study used a descriptive qualitative method to describe the English sounds that were causing the students' pronunciation problems. The information gathered served as a record for the students. The researcher used The Oxford Learner's Pocket Dictionary and the theory of English phonetics and phonology proposed by Peter Roach and George Yule to convey the accuracy of the analysis. The total spelling correctly by the research subject was 293 times sounds (53,4 %) and the total spelling incorrectly by the subjects were 255 times sounds (46,6 %), the highest spelling correctly by the student P is 95,8 % and the highest spelling incorrectly by the student L is 95 %, and 8 of 20 subjects could pronounce the sounds correctly.